Ways to increase the inter-maitenance period of roads - A. A. Lytkin; G. V. Dolgikh; A. S. Prolygin (Вестник СибАДИ)
Introduction. Currently, more than 96% of the roads in our country are built with non-rigid pavements with bases made of dispersed materials of crushed stone, sand-gravel mixtures, sand, etc. Significant disadvantages of such road structures are high material consumption and significant operating costs, including those associated with low service life between repairs. According to expert estimates, Russia’s losses due to the poor quality of the highway network amount to 3% of gross domestic product. In 2017, the government decided to increase service life between repairs of federal highways, for example, for major repairs from 12 to 24 years. To solve the problem of increasing the time between repairs, it is necessary to ensure a significant increase in the total modulus of elasticity on newly constructed or repaired roads. One of the effective ways to increase the strength characteristics of non-rigid road pavements is the wider use of monolithic bases made from soils or asphalt granulate treated with mineral binders, as well as industrial wastes with own binding properties. Replacing bases made of dispersed materials with monolithic ones makes it possible to reduce the material consumption of road pavement by 20-50%, the cost of construction work by up to 45% and increase the service life of roads by 35-40%.Materials and methods. In order to study the influence of the type of filler on the processes of structure formation of sludge crushed stone material, research on the strengthening of granite crushed stone of the 0-15 mm fraction and crushed stone from low-active blast furnace slag, 15% nepheline sludge was carried out. Samples with a diameter and height of 7 cm from mixtures of optimal humidity by pressing under a load of 15 MPa were formed. The samples under normal conditions and tested at the ages of 1, 3, 6 and 9 months to determine the compressive and tensile strength in bending were stored. In order to determine the optimal dosages of sludge for strengthening slag crushed stone, samples with a sludge content of 5, 10, 20, 30% were formed using a similar method and tested for compression and splitting immediately after production and then after 1, 3, 6, 9 and 12 months hardening. When examining experimental sections of transitional type coatings at the first stage of construction of oil field roads, the total elastic moduli were determined using a MADI-TsNIL deflectometer and a loaded MAZ-500A vehicle. To study the hardening kinetics of sludge-granular concrete from asphalt granulate, reinforced with ground sludge, samples with a diameter of 71.4 mm by pressing under a pressure of 7 MPa, according to standard methods were prepared. The series of samples differed in the dosage of ground sludge (10℅ and 15℅) and their hardening conditions. The samples under normal conditions and in natural conditions (in the open air) in a box with sand, to simulate the temperature regime of hardening of the material in the base of the road pavement and tested at the age of 7, 28, 90, 180 and 360 days at temperatures of 200C and 500C were stored.Results. The analysis of normative and literary sources on the issues of increasing the interrepair service life of highways is carried out. Separate proposals for amending current regulatory documents for public discussion are given. The physico-chemical and physico-mechanical properties of belite sludge – large-tonnage waste from alumina production – are presented. The scope of their application in the construction, reconstruction and repair of highways is shown. The high efficiency of using belite sludge as a slow-hardening binder in order to extend the service life of roads during the construction of monolithic bases and transitional coatings has been theoretically substantiated and experimentally confirmed. Rational pavement designs for the construction of oil field roads in the swampy regions of Siberia with the replacement of prefabricated reinforced concrete pavements at the first stage of construction with monolithic transitional pavements made of stone materials reinforced with belite sludge have been developed. Laboratory and experimental research to justify the replacement of traditional binders with ground nepheline sludge when repairing asphalt concrete pavements using the cold recycling method with an extension of the construction season were carried out.Сonclusion. Over the past 30 years, the number of heavy vehicles has significantly increased on the roads of Russia. At the same time, the requirements for the service life between repairs of flexible road pavements have increased. Increasing service life, in principle, is quite possible, but requires the introduction of innovative design solutions at the design, construction, reconstruction and repair stages using highly efficient materials and technologies in order to significantly increase the total elastic modulus, in particular by replacing road pavement bases made of dispersed materials with monolithic ones. It is necessary to more widely introduce technologies for constructing foundations from local soils treated with mineral binders (cement, lime, active fly ash, etc.), as well as industrial waste with independent binding properties, for example belite sludge. In addition, it is necessary to continue research on the development of complex slow hardening non firing, including geopolymer binders based on industrial waste specifically for strengthening soils and stone materials with the development of regulatory documents in the development of TR CU 014/2011. When repairing and overhauling roads to restore the bearing capacity of layers of crushed stone (gravel) bases and strengthening flexible road pavements, preference should be given to the cold regeneration method. At each stage of the life cycle of highways, there are reserves for increasing the time between repairs that must be implemented.